LITERASI DIGITAL: MANAJERIAL KELAS ONLINE BAGI TENAGA PENDIDIK [DIGITAL LITERACY: ONLINE CLASS MANAGERIAL FOR EDUCATORS] - Stella Stefany; Rijanto Purbojo; Clarissa Adeline (Jurnal Sinergitas PKM & CSR, 2020)
The COVID-19 pandemic emerging in early 2020 has significantly impacted various sectors, including education. The policy of home-based learning (defined as online learning), that is implemented by the Indonesian Ministry of Education and Culture becomes a challenge for students, teachers, and educational institutions. Online-based learning is still an unfamiliar concept to the world of education in Indonesia. Lack of preparation and planning during the switch to online-based learning leads to bad learning experiences for both students and teachers alike. This event was aimed towards Indonesian educators to discuss essential elements regarding digital literacy competence, namely basic principles of distinguishing face-to-face classes and online classes, deciding on a format, design, and interaction in online classrooms, as well as the cycle of teaching and learning. As many as 454 participants from the five major islands in Indonesia virtually attended this event on May 13th, 2020. This event utilizes the ADDIE training developmental model elaborated in five stages: 1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. BAHASA INDONESIA ABSTRACT: Pandemi COVID-19 yang muncul di awal tahun 2020 memberi dampak signifikan dalam berbagai sektor, termasuk Pendidikan. Kebijakan home-based-learning atau pembelajaran jarak jauh yang ditetapkan oleh Kementrian pendidikan dan Kebudayaan Indonesia menjadi sebuah tantangan bagi peserta didik, tenaga pendidik dan institusi pendidikan. Pembelajaran berbasis daring masih asing bagi dunia pendidikan di Indonesia. Kurangnya persiapan dan perencanaan dalam kegiatan belajar mengajar daring berakibat pada pengalaman belajar-mengajar yang buruk bagi peserta didik maupun tenaga pendidik. Kegiatan ini ditujukan bagi tenaga pendidik di Indonesia untuk membahas beberapa elemen penting dalam kompetensi literasi digital seperti prinsip dasar yang membedakan kelas tatap muka dengan kelas daring, menentukan format, desain dan interaksi kelas daring, serta siklus belajar mengajar berbasis daring. Kegiatan ini diikuti oleh 454 partisipan yang tersebar pada lima pulau terbesar di Indonesia berlangsung secara virtual pada tanggal 13 Mei 2020. Kegiatan ini menggunakan model pengembangan training ADDIE dengan 5 tahapan sebagai berikut: 1) Analyze, (2) Design, (3) Development, (4) Implementation dan (5) Evaluation.